Dynamic Dependency-Based Purity Checking (Artifact) - Risberg Alaküla, Anton ; 0000-0003-0814-3367; Fors, Niklas ; 0000-0003-2714-9457; Reichenbach, Christoph ; 0000-0003-0608-7023 (Zenodo, 2025)
This is the software artifact for the paper "Dynamic Dependency-Based Purity Checking" published in ACM SIGPLAN International Conference on Software Language Engineering (SLE) 2025. The artifact was reviewed and awarded with the badges "Available" and "Reusable" (see https://www.acm.org/publications/policies/artifact-review-and-badging-current).